The development of Geogebra-based calculus e-modul assisted by Moodle website - Mohammad Rifa'i; Roisatun Nisa' (Math Didactic: Jurnal Pendidikan Matematika, 2019)
This research discusses the development of geogebraic calculus-based e-modules using the support of Moodle website. This study aims to determine the feasibility level (quality) of e-modules from experts and also to determine the response of users (students) to the e-module calculus that was developed. The research methods used in this case include: planning (needs analysis), design, development, validation, and implementation (application). The data collection technique is done by using a validation sheet as an instrument to assess the feasibility (quality) of e-modules by media experts and material experts. In addition, the response questionnaire sheet is used to view responses from e-module users. The results obtained showed that the validation score of the media expert was 34 or included in the excellent category, with the percentage of overall ideals being 85.00%. Then, the validation score of the material expert is 49 or is in the very good category, with the percentage of overall ideals being 87.50%. While the results of trials on 20 students obtained a very positive response with a percentage of 90 %.